Sampling frame for crop area estimation - Adami, Marcos; Moreira, Mauricio Alves; Rudorff, Bernardo Friedrich Theodor; Freitas, Corina da Costa; Faria, Rogério Teixeira de; Deppe, Flavio (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to develop a methodology in order to use remote sensing and Geographic Information System (GIS) to construct a sampling frame and to allocate regular segments in a region through a random stratified sampling system. The different strata were obtained through satellite image classification. In each stratum a drawing was carried out to select sample segments, which were field visited to identify the crop type and to estimate their area. In the area estimation for each crop, for the entire region, the direct expansion estimator through a semi-automated procedure was used . The methodology reduced both the subjectivity of the percentage of agricultural area estimation in the strata and the time to construct the sampling frame.